Podcasting - Morris, Tee 1968-; Tomasi, Chuck (John Wiley & Sons, Inc., 2024)
Ever wonder what it takes to get your very own podcast up and running? How to get the gear you need, pick a great topic, secure fascinating guests, and assemble it all into a refined and irresistible product? Well wonder no more! Because Podcasting For Dummies has the essential guidance you need to get your brand-new podcast up and running. From selecting the right recording equipment to identifying an audience and pro-level production tips, you'll find all the killer info to help you get started on your next big idea.
Includes bibliographical references and index
Keywords: Podcasting; Internet radio broadcasting; Webcasting; Sound -- Recording and reproducing; Baladodiffusion; Radio sur Internet; Webdiffusion; Son; Enregistrement et reproduction